2021
DOI: 10.1177/1528083721993775
|View full text |Cite
|
Sign up to set email alerts
|

Heat and moisture transfer properties of a firefighter clothing with a new fire-resistant underwear

Abstract: Under dynamic wear conditions, moisture management and heat transfer behaviour of clothing between the human body and its environment are very important attributes for comfort and performance. Especially considering heavy works like firefighting, it is important to analyse liquid moisture management and thermal comfort properties of fabrics that influence moisture sensation and personnel comfort feeling significantly. This study mainly investigates thermal comfort and moisture management properties of a firefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The decreasing of SF1 and SF2 indicated that the moisture (sweat) evaporates and takes away the thermal energy, which means the moisture played a significantly positive role for MMP + fabrics during the exposure. 54,55 When the sweat rate increased from SR10 to SR19, a more significant relative decreased rate of unit sweat rate (∆EAE SR19-10 * = (EAE SR19 -EAE SR10 )/EAE SR10 /(19-10)) occurred for SF1 (−0.78%) than SF2 (−0.11%). This phenomenon could be explained by the differences in the in-plane and trans-planar wicking of liquid moisture, 56 which is related to the moisture transfer performance among various fabric types.…”
Section: Resultsmentioning
confidence: 99%
“…The decreasing of SF1 and SF2 indicated that the moisture (sweat) evaporates and takes away the thermal energy, which means the moisture played a significantly positive role for MMP + fabrics during the exposure. 54,55 When the sweat rate increased from SR10 to SR19, a more significant relative decreased rate of unit sweat rate (∆EAE SR19-10 * = (EAE SR19 -EAE SR10 )/EAE SR10 /(19-10)) occurred for SF1 (−0.78%) than SF2 (−0.11%). This phenomenon could be explained by the differences in the in-plane and trans-planar wicking of liquid moisture, 56 which is related to the moisture transfer performance among various fabric types.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Eryuruk et al [18] investigated the thermal comfort and moisture management of a firefighter garment with a new fire-resistant underwear. They analyzed the performance characteristics of single-layer fabrics (underwear, outer shell, moisture barrier, and thermal barrier) and their three-and four-layer combinations to better understand comfort and protective performance.…”
Section: State Of Researchmentioning
confidence: 99%
“…The results showed that although the disguised materials had good thermal protection, they improved the thermal hazard. Chen 15 17 analyzed the heat transfer of protective clothing through FPGA simulation software and temperature sensor, and verified the transfer model by comparing with the experimental data. In their research, the thermal comfort performance of protective clothing was optimized, which could protect the skin from the thermal damage caused by low-intensity thermal radiation.…”
Section: Introductionmentioning
confidence: 97%